2013
DOI: 10.1021/ja407059n
|View full text |Cite
|
Sign up to set email alerts
|

Monothiol Glutaredoxins Can Bind Linear [Fe3S4]+ and [Fe4S4]2+ Clusters in Addition to [Fe2S2]2+ Clusters: Spectroscopic Characterization and Functional Implications

Abstract: Saccharomyces cerevisiae mitochondrial glutaredoxin 5 (Grx5) is the archetypical member of a ubiquitous class of monothiol glutaredoxins with a strictly conserved CGFS active-site sequence that has been shown to function in biological [Fe2S2]2+ cluster trafficking. In this work, we show that recombinant S. cerevisiae Grx5 purified aerobically after prolonged exposure of the cell-free extract to air or after anaerobic reconstitution in the presence of glutathione, predominantly contains a linear [Fe3S4]+ cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 61 publications
2
51
0
Order By: Relevance
“…In combination with other spectroscopic techniques, RR has revealed the details about the cluster formation, type and coordination along these processes. The studied systems include proteins that are stress-responsive transcriptional regulators, and/or participate in iron metabolism, such as BolA proteins and homologues [8, 39]. Among the latter is Fra2, which plays a key role in regulating the iron homeostasis in yeasts.…”
Section: Rr Spectroscopy Of Fe–s Proteins and Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…In combination with other spectroscopic techniques, RR has revealed the details about the cluster formation, type and coordination along these processes. The studied systems include proteins that are stress-responsive transcriptional regulators, and/or participate in iron metabolism, such as BolA proteins and homologues [8, 39]. Among the latter is Fra2, which plays a key role in regulating the iron homeostasis in yeasts.…”
Section: Rr Spectroscopy Of Fe–s Proteins and Enzymesmentioning
confidence: 99%
“…After “Introduction”, we will first briefly describe the basics of RR spectroscopy of Fe–S proteins, together with the most commonly used approaches for determination of their redox properties. Then we will focus on the major contributions of RR spectroscopy in the studies of diverse Fe–S proteins, such as those that participate in ET [1, 1321], DNA repair [11], biogenesis of Fe–S clusters [3, 2230] and heme cofactors [31], substrate binding and activation, S-donation and catalysis [3235], and regulation of gene expression [5, 8, 10, 3639]. We will conclude with several examples of recent RR studies of enzymes carrying complex polychromophoric clusters [7, 40, 41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important difference is that yeast Grx5p contains an additional cysteine residue (C 90 or C 117 including the targeting sequence) implicated in intramolecular disulfide exchange reactions (15). Whereas genetic analyses indicated that this cysteine does not seem essential for ISC biogenesis (25), Zhang et al showed in mutational studies that this cysteine is required for the assembly of Fe 4 S 4 cluster and that the Fe 4 S 4 cluster-bound form of Grx5p is competent for restoring the activity of recombinant ACO in vitro (17). Although this cysteine is present in most algal isoforms, it is replaced by a serine in orthologs from terrestrial plants, except Selaginella moellendorffii (26).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the visible part of the absorption spectrum of the reconstituted protein presented a prominent absorbance peak at approximately 420 nm compared with the apoprotein (Fig. 4A) + clusters (17). Next, we evaluated the capacity of GRXS15 to transfer its ISC to an acceptor protein.…”
Section: Recombinant Grxs15 Lacks Oxidoreductase Activity But Binds Anmentioning
confidence: 98%